Variación estacional en la proporción relativa de los estadios de la oogénesis en Bufo arenarum (Anura: bufonidae) - Echeverría, Dinorah Diana (1994)
The Anova repeated measure design was used to compare the percentage of oocytes in female toads (Bufo arenarum) at stages 1 to 5 and at different physiological ovary periods (or phases: production, before ovulation, after ovulation). Individual comparisons among stages and between phases have been made with the minimum significant difference method at 0.05 probability level. The statistical analysis at percentage of oocytes showed that: a) Stages 1 and 2 have few variation. They are the permanent oocytes group. b) Stage 3 (late vitelogenesis oocytes) are absent previous to the breeding season. Their rate increases in summer and decreases in autumn. The development of oocytes 3 take place afterwards the ovulation. c) Stage 4 increases in autumn and disappears in late winter. d) Stage 5 sets up as the 18% of the ovulated oocytes. e). Stages 3, 4 and 5 are renewed every year; they are temporary ovarian oocytes.